Account Transfer Practices in Online Transportation Services Reviewed from the Perspective of Business Ethics and Islamic Transactions - Alya Nur Mutmainah; Geger Permana; Ula Nazhiatul Mardiyah; Jaenudin J; Dian Herdiana (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The rapid development of digital technology has transformed Indonesiaâ€™s online transportation sector, including the rise of account-sharing practices among platform drivers. This study analyzes account lending in ShopeeFood services through a qualitative descriptiveâ€“interpretive approach using observation, semi-structured interviews, and documentation. Findings indicate that account sharing is primarily driven by economic pressures and administrative barriers, yet it creates ethical issues such as identity mismatch, security risks, and potential moral hazard. From an Islamic business ethics and muamalah perspective, the practice involves elements of gharar and tadlis due to ambiguity in contract execution, violating the principles of á¹£idq, amÄnah, and al-â€˜adl. Despite this, informants displayed ethical awareness and willingness to comply with legal mechanisms if more accessible registration pathways were available. The study highlights the need for stronger regulatory literacy, improved identity verification systems, and the integration of Islamic ethical values in digital platform governance. Overall, this research contributes to understanding the ethical implications of account lending and provides normative recommendations for platform companies and Muslim users in fostering integrity-based digital business practices.